Upcycling of carbon, nitrogen, and phosphorus from aquaculture sludge using the polychaete Hediste diversicolor (OF Müller, 1776) (Annelida: Nereididae) - Anglade, Inka; Kristensen, Bjørn S. B.; Dahl, Thomas H.; Hagemann, Andreas; Malzahn, Arne M.; Reitan, Kjell Inge (Frontiers in Sustainable Food Systems, 2023)
Introduction Focusing on circular bioeconomy and finding solutions for managing finite and scarce resources such as phosphorus are issues that need to be addressed across sectors to attain food security. Land-based aquaculture of Atlantic salmon (Salmo salar L.) smolt and post-smolt results in a large output of aquaculture sludge. These nutrient-rich side streams from aquaculture production constitute a valuable resource for cultivation of polychaetes Hediste diversicolor. The aim of this study was to evaluate the capacity of H. diversicolor to upcycle carbon (C), nitrogen (N), and phosphorus (P) contained in aquaculture sludge from Norwegian salmon production. Material and methods We investigated the effect of two diets, smolt sludge and post-smolt sludge, which were supplied at four different feed levels, on the gain of C, N, and P in H. diversicolor and established uptake rates for the upcycling of these nutrients. Additionally, we examined how different feed composition (type of diet) and supply (feel level) influenced C, N, and P content as well as the elemental ratios of H. diversicolor. Results and discussion Polychaetes fed with both types of sludge were shown to incorporate C, N, and P from their diets into biomass. Incorporation of C, N, and P in polychaete biomass was highest at the highest feed levels, following specific growth rates. Uptake of diet C, N, and P into polychaete biomass was similar for both diets and across feed levels. On average, C and N uptake rates amounted to 2–10% and 2–15%, respectively, while values for P uptake were lower at 0.5–1.5%. C, N, and P content of polychaetes was not affected by different diets or feed levels while the C:N ratio increased with increasing feed supply. Overall, we found that H. diversicolor can successfully take up nutrients contained in aquaculture sludge and thus can be beneficial for upcycling of side streams from Atlantic salmon production.